1002 Calcium administration in Major haemorrhage Protocol. (4th May 2021) - Akhtar, A; O'Connor, R; Rosen, J; Brooks, A
Abstract: Introduction: Calcium gluconate is an essential part of the major haemorrhage protocol (MHP). It minimizes the exacerbation of transfusion coagulopathies due to the citrate preservative. As fifty percent of trauma patients present with hypocalcaemia prior to transfusion, the risk is pertinent. Given the importance of the issue, surprisingly current guidelines remain sparse. We analysed the percentage of patients who received calcium and their hypocalcaemia incidence. Method: A Retrospective review of red traumas during June to August 2019. The frequency of MHP and the patient's ionised plasma calcium levels on VBG (1.15-1.26mmol/L) were identified. Our standard stated 100% of MHP should receive calcium. A massive transfusion was defined as 10 red blood cells units in 24 hours or 4 blood products within 30mins. Results: 27 red traumas were accepted to audit, MHP was activated in 85%. Out of these 75% received calcium and on average after 6.4 units of blood products. The incidence of ionised hypocalcaemia in all MHP patients was 67%. Conclusions: We identified a standard that supplementary calcium should be supplemented in all MHPs. Hypocalcaemia was more frequency than our research stipulated. Improvement needs to be made to meet standards. We recommend incorporation of Calcium gluconate into major haemorrhage pack and transfusion guidelines.